Langevin simulation of scalar fields: Additive and multiplicative noises and lattice renormalization - Cassol-Seewald, N. C. [UNESP]; Farias, R. L. S.; Fraga, E. S.; Krein, Gastão Inácio [UNESP]; Ramos, Rudnei O. (Elsevier B.V., 2012)
We consider the Langevin lattice dynamics for a spontaneously broken 44 scalar field theory where both additive and multiplicative noise terms are incorporated. The lattice renormalization for the corresponding stochastic Ginzburg-Landau-Langevin and the subtleties related to the multiplicative noise are investigated. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Langevin dynamics; Lattice renormalization; Multiplicative noise